2018
DOI: 10.1186/s12889-018-5992-6
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviours of Australian men and the likelihood of attending a dedicated men’s health service

Abstract: BackgroundRedesigning primary health services may enhance timely and effective uptake by men. The primary aim of this study was to assess the likelihood of Australian men attending a dedicated men’s health service (DMHS). The further aims were to better understand the reasons for their preferences and determine how health behaviours influence likelihood.MethodsA survey on health service use and preferences, health help-seeking behaviours, and the likelihood of attending a DMHS was administered by telephone to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Unlike programs that have historically achieved advances, such as maternal and child health, the man’s health program is a recent policy, necessitating, therefore, strategies that will qualify future nurses to intervene in the health of this population. In this sense, studies ( 26 - 27 ) have indicated low adherence of men to health services, which raises, in the undergraduate curricular strategies transversal on the health of the man and programs of permanent education in service.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike programs that have historically achieved advances, such as maternal and child health, the man’s health program is a recent policy, necessitating, therefore, strategies that will qualify future nurses to intervene in the health of this population. In this sense, studies ( 26 - 27 ) have indicated low adherence of men to health services, which raises, in the undergraduate curricular strategies transversal on the health of the man and programs of permanent education in service.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current data provide a rationale for incorporation of reproductive urology into the men's health center umbrella. This is particularly important, as prior studies have demonstrated that men are more likely to engage with the healthcare system when offered the opportunity for treatment at a dedicated men's health clinic (25). We also found that semen parameters, including TMSC, were slightly higher among men reporting an established PCP, although the statistical significance of this comparison decreased upon sensitivity analysis.…”
Section: Discussionmentioning
confidence: 45%
“…The decision for men to formally seek health information or services is often delayed by a period of self-monitoring and is dependent on the perceived seriousness of the symptoms experienced ( Smith et al ., 2008a ; Yousaf et al , 2015 ; Adam et al ., 2019 ). When men do attend health services, they seek support later in their illness, leave significant health issues unattended and are more likely to somatize psychological concerns ( Vincent et al ., 2018 ). These patterns of engagement with health services appear to be especially prominent amongst young men ( Rickwood et al ., 2005 ; Rice and Baker, 2017 ; Vincent et al ., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…When men do attend health services, they seek support later in their illness, leave significant health issues unattended and are more likely to somatize psychological concerns ( Vincent et al ., 2018 ). These patterns of engagement with health services appear to be especially prominent amongst young men ( Rickwood et al ., 2005 ; Rice and Baker, 2017 ; Vincent et al ., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation